2020
DOI: 10.1186/s13054-020-02860-3
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoproteins during sepsis: from bench to bedside

Abstract: High-density lipoproteins (HDLs) represent a family of particle characterized by the presence of apolipoprotein A-I (apoA-I) and by their ability to transport cholesterol from peripheral tissues back to the liver conferring them a cardioprotective function. HDLs also display pleiotropic properties including antioxidant, anti-apoptotic, antithrombotic, anti-inflammatory, or anti-infectious functions. Clinical data demonstrate that HDL cholesterol levels decrease rapidly during sepsis and that these low levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
164
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 107 publications
4
164
0
1
Order By: Relevance
“…In this study, HDL-C levels of adult COVID-19 patients were lower than normal at admission, which was similar to previous researches. Several studies showed infected patients, especially those with sepsis, always had a signi cant drop in HDL levels [10,12,15,20,21,22], but the reason for the decline in HDL level remained unexplained. However, several hypotheses are considered to be possible, including a decrease in HDL synthesis, overconsumption or redistribution of HDL particles from intravascular to the extravascular space [10,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, HDL-C levels of adult COVID-19 patients were lower than normal at admission, which was similar to previous researches. Several studies showed infected patients, especially those with sepsis, always had a signi cant drop in HDL levels [10,12,15,20,21,22], but the reason for the decline in HDL level remained unexplained. However, several hypotheses are considered to be possible, including a decrease in HDL synthesis, overconsumption or redistribution of HDL particles from intravascular to the extravascular space [10,23].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that HDL-C can bind and neutralize the biological toxicity of lipopolysaccharide (LPS) and lipoteichoic acid (LTA) [32,33,34]. In different experimental septic models, infusion of reconstituted HDL reduced in ammation, decreased bacterial count, attenuated organ injury and improved survival [10,35,36], which greatly encouraged the application of HDL in sepsis treatment in the future. However, the role of HDL-C in viral infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that serum ApoA1 was associated with the outcome of patients with sepsis and acute respiratory distress syndrome induced by pneumonia, as well as critically ill patients [13][14][15][16]. In acute in ammatory disease, serum amyloid A (SAA), an acute phase protein, displaces ApoA1 from the HDL complex; then, free ApoA1 is easily eliminated by the kidney, resulting in low levels in the peripheral blood [17]. On the other hand, liver is susceptible to attack by SARS-CoV-2, especially in severe cases [18]; therefore, reduced synthesis by the injured liver may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Septic patients exhibit a marked reduction in plasma HDL level and the low level of HDL cholesterol is a poor prognostic factor for severe sepsis [10][11][12]. In addition, an adverse transition of HDL to pro-inflammation was observed during acute inflammatory disorder diseases including sepsis [13][14][15]. Previous studies indicated that the abnormal oxidation of apoA-I by the myeloperoxidase (MPO) could be one of potential causes for the adverse transition of HDL in acute phase [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an adverse transition of HDL to pro-inflammation was observed during acute inflammatory disorder diseases including sepsis [13][14][15]. Previous studies indicated that the abnormal oxidation of apoA-I by the myeloperoxidase (MPO) could be one of potential causes for the adverse transition of HDL in acute phase [13,16]. However, due to the complexity of HDL subfractions, the adverse remodeling of HDL in pathogenesis of septic ARDS is large unknown.…”
Section: Introductionmentioning
confidence: 99%